ASSESSMENT OF INEQUALITY TO FOREST RESOURCES ACCESS IN THE CONTEXT OF SUSTAINABLE RURAL DEVELOPMENT - Ivan OPENKO; Oleksandr SHEVCHENKO; Ruslan TYKHENKO; Oleg TSVYAKH; Yuliia MOROZ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current trends in rural development, sustainable use of nature, provision of comfortable ecological, economic and social conditions for the life of the population determine the solution to the problem of inequality within the respective state and between the countries as a whole. According to the results of the study of equality of supply with natural resources, in particular, forest land we have found that the greatest imbalance in the generation of gross income from the use of forest land is determined in the Steppe natural and climatic zone (GINI = 0,53) and the Kyiv and Sumy regions, the northern part of which is located in the Polissya zone, and the southern part of the administrative unit is located in the Forest-steppe zone (GINI = 0,92). It should be noted that on all other indicators the calculated Gini index indicates a low inequality in the provision of natural resources to the population, in particular, forestry lands in the context of all natural and climatic zones of Ukraine, which is a favorable factor for rural development, the formation of environmentally-safe conditions people living and decentralization. With the help of Gini index (inequality), it is possible to formulate a conceptual direction of transformation of ecological and economic mechanisms of forest land use, the mainstream of which should approach absolute equality in providing the population with natural resources, in particular, forestry, distribution of economic income from the implementation of forestry production. safe environment and social living conditions of people in newly created UTC.